Research on neuroprotective effects of a fusion protein of omega-conotoxin mviia and thioredoxin - Huyen, Bui Thi; Binh, Doan Viet; Kim Dung, Nguyen Thi; Bich Thao, Le Thi; Nhi, Nguyen Bich; Chi, Phan Van (Academia Journal of Biology, 2013)
Ischemic stroke is one of the most dangerous human diseases. Blood supply to the brain is decreased initiating the ischemic cascade with the consequence of a Ca2+ influx into nerve-cells. This Ca2+ influx can than cause neuronal injury or death of cells. Omega-conotoxin MVIIA (omega-CTX) is a neurotoxin isolated from the venom of Cone snail Conus magus. It is a potent selective blocker of the N-type voltage-sensitive calcium channel in neurons and therefore has the potential to promote neuroprotection through inhibition of Ca2+ influx into nerve-cells. Omega-CTX has been cloned, expressed in the fusion form with thioredoxin (Trx-CTX ) in E. coli in the institute of biotechnology, Hanoi. In this paper we present our study on neuroprotectiv activity of Trx-CTX in mouse model of global cerebral ischemia and focal brain ischemia. The experiments were carried out in male mice of Swiss race weighing 40 g. Trx-CTX were injected i.v. in the model of global cerebral ischemia, one time with a dose of 5 or 10 mg/kg and in the other model two times, each with a dose of 5 mg/kg. The results showed that in global cerebral ischemia Trx-CTX has decreased neuronal injury and death of CA1 cells of dorsal hippogampus. In other model Trx-CTX also decreased infarction size of the ischemic brain. Trx-CTX proof to possess neuroprotective effect and could be used in further researchs for medicinal purpose.